2016
DOI: 10.1111/ped.13086
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of neonatal mortality in rural and urban Nigeria: Evidence from a population‐based national survey

Abstract: Determinants of neonatal mortality were different in rural and urban Nigeria, and rural neonates had greater risk of mortality than their urban counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 26 publications
7
39
0
1
Order By: Relevance
“…A further analysis of 2013 Nigeria DHS showed a difference in neonatal mortality between the urban and rural population. The risk factors for neonatal mortality in urban population was lack of electricity (AOR 1.56; 95% CI 1.09-2.22), small birth size (AOR 3.05, 95% CI 2.05-4.54), and male gender (AOR 1.67, 95% CI 1.22-2.23) (Adewuyi and Zhao 2017). A further analysis of the 2012-2013 Pakistan DHS showed that employed mothers had higher odds of neonatal mortality (OR 1.47) while women living in consanguineous marriages had higher odds of infant mortality (OR 1.45) and under-five mortality (OR 1.38).…”
Section: Discussionmentioning
confidence: 99%
“…A further analysis of 2013 Nigeria DHS showed a difference in neonatal mortality between the urban and rural population. The risk factors for neonatal mortality in urban population was lack of electricity (AOR 1.56; 95% CI 1.09-2.22), small birth size (AOR 3.05, 95% CI 2.05-4.54), and male gender (AOR 1.67, 95% CI 1.22-2.23) (Adewuyi and Zhao 2017). A further analysis of the 2012-2013 Pakistan DHS showed that employed mothers had higher odds of neonatal mortality (OR 1.47) while women living in consanguineous marriages had higher odds of infant mortality (OR 1.45) and under-five mortality (OR 1.38).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable logistic regression analyses were conducted to examine the adjusted association between the outcome variable and the independent variables using the hierarchical modelling method [5,19].…”
Section: Discussionmentioning
confidence: 99%
“…Such data disaggregation approach may help capture context-specific factors which could be lost to the use of 'one-size-fits-all' method of pooled datasets [7,19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the determinants of use/non-use of healthcare facility for childbirth in Nigeria,10 17–21 and have reported a significant association between place of delivery and a range of sociodemographic factors including rural-urban residence, maternal/husbands education level, maternal religion, wealth index, region of residence, maternal age and birth order. However, to date, available studies have focused mainly on factors associated with institutional delivery among all mothers of reproductive age (aged 15–49 years).…”
Section: Introductionmentioning
confidence: 99%
“…Achieving universal health coverage and reducing the global burden of maternal as well as neonatal mortalities are major health-related targets of the recently launched Sustainable Development Goals (SDGs) 30. These targets are a high priority in Nigeria considering the poor indices of maternal and newborn health outcomes in the country 8 19 29. From 2015 through to 2030, an estimated 1.6 million maternal lives are at stake and Nigeria alone is projected to account for about 33.3% of this estimate 31.…”
Section: Introductionmentioning
confidence: 99%